2016
DOI: 10.1177/0954405415569817
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off among mechanical properties and energy consumption in multi-pass friction stir processing of Al7075 alloy employing neural network–based genetic optimization

Abstract: Friction stir processing is a novel material processing technique. In this study, neural network-based genetic optimization is applied to optimize the process performance in terms of post-friction stir processing mechanical properties of Al7075 alloy and the energy cost. At first, the experimental data regarding the properties (i.e. elongation, tensile strength and hardness) and the consumed electrical energy are obtained by conducting tests varying two process parameters, namely, feed rate and spindle speed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The processing zones using FSP were prone to defects such as crack, voids and air bubbles because of insufficient or excess heat input. 24 Saeedy et al 25 found that the heat input was proportional to the inverse of traverse speed. Increasing the transverse speed would decrease the maximum temperature and the amount of molten material inside the processed zone but increase the heating and cooling rates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processing zones using FSP were prone to defects such as crack, voids and air bubbles because of insufficient or excess heat input. 24 Saeedy et al 25 found that the heat input was proportional to the inverse of traverse speed. Increasing the transverse speed would decrease the maximum temperature and the amount of molten material inside the processed zone but increase the heating and cooling rates.…”
Section: Methodsmentioning
confidence: 99%
“…As a complex process, FSP included non-uniform material flow. 24 The character of the processed zone was affected by the tool parameter and process parameter which dictated the overall heat input. In FSP, the ''processing time,'' the time during which the material has undergone the thermalmechanical influence, was influenced by transverse speed.…”
Section: Morphology Analysesmentioning
confidence: 99%
“…The optimization can be performed either employing statistical techniques or artificial intelligence algorithms. It has been shown in previous studies for similar tasks that the results of statistical techniques have not been so promising, for instance in mechanical [22] and civil engineering [23], among others. In these cases, using an AI-based technique such as artificial neural network (ANN) [24] or support vector regression (SVR) [25] has shown better results.…”
Section: Contributionsmentioning
confidence: 99%
“…5 As far as the welding of metals is concerned, friction stir welding (FSW) is receiving more and more interest owing to the energy efficiency, environmental friendliness and versatility that make this process a promisingly ecologic and 'green' technology. [6][7][8][9][10] It is thought that FSW consumes less energy as compared with fusion welding technologies due to the lower temperatures involved and the solid-state nature of the process. [11][12][13][14][15] Heurtier et al found that the heat inputs for gas metal arc welding (GMAW) and gas tungsten arc welding (GTAW) are 2 and 1.5 times higher than that for FSW, respectively.…”
Section: Introductionmentioning
confidence: 99%